Function of Sox2 as a transcriptional repressor - Liu, Yu-Ru (2011)
Sox2 is one of the earliest known transcription factors to be expressed during development of the nervous system (Rex et al., 1997; Silvia Brunelli, 2003; Wang et al., 2006b; Dee et al., 2008). Ectodermal cells expressing Sox2 have the potential to differentiate into nerve cells. Cells expressing Sox2 are specified to a neural fate during neural induction. Sox2 belongs to the SoxB1 family, comprising Sox1, Sox2 and Sox3, which are generally considered to activate specific target genes, whereas, the SoxB2 group, Sox14 and Sox21, act as transcriptional repressors (Uchikawa, Kamachi, & Kondoh, 1999). However, Sox2 has also been demonstrated to act as a repressor (Kopp et al., 2008) which implies that Sox2 could have a dual-function in vivo. Previous studies indicated that the HMG box-containing protein, Tcf/Lef, interacts with the transcriptional co-repressor, Groucho (Helen Brantjes, 2001). We therefore set out to determine if interaction with the Groucho co-repressor could also explain the repressor ability of Sox2. In this study, we have examined the interaction between Sox2 and Groucho using nuclear translocation, yeast-two-hybrid and co-immunoprecipitation assays. The data suggest that Sox2 interacts with Groucho through a C-terminal, engrailed-like motif. The effect of Groucho on Sox2 function was measured using a luciferase reporter assay. The transcriptional activation activity of Sox2 was repressed after co-expressing with Groucho. To address the biological function of Sox2-Groucho interaction, a loss-of-repressor-function mutant of Sox2 was created by point mutating the essential engrailed-like motif. Analysis in Zebrafish embryos indicated that the of loss-of-repressor-function mutant of Sox2 (Sox2LQY/AAA) lost the ability to repress the expression of chordin. In human neural stem cells, Affymetrix arrays revealed that 676 genes were activated and 786 genes were repressed by Sox2 overexpression. Within the genes that were repressed by Sox2, approximatly 7% were less repressed by Sox2LQY/AAA. Together, these data suggest that Sox2 functions not only as a transcriptional activator but also as a repressor through interacting with the corepressor Groucho. However, because only 7% of the repressed genes were affected by the Sox2LQY/AAA mutant, this suggests that there are other mechanisms involved in Sox2 transcriptional repressor function.